Analisis Tindak Tutur Direktif dalam Daftar Putar Video Taman Edukasi: Kenalan sama Animasi dalam Kanal Youtube Kok Bisa? - Muhammad Rizal Rusdi; Febriyani Kusumaningrum; Octa Surya Pradana; Tulus Eko Sriyandoyo; Lintang Kusumaningrat; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Zuhrul Anam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In the current digital era, learning videos have become a popular alternative for delivering information and teaching materials. Therefore, it is important to analyze the effectiveness of speech acts, especially directive speech acts used in educational videos. The purpose of this study is to analyze and realize the number of speech acts, namely in directive speech acts in the Playlist of Taman Edukasi: Kenalan sama Animasi in the youtube channel Kok Bisa?. The approach used in this research is pragmatic theoretical approach and descriptive qualitative. Researchers used listening and recording techniques on the Taman Edukasi: Kenalan sama Animasi in the youtube channel Kok Bisa?. The researcher used descriptive qualitative method of research based on postpositive philosophy which is used to study natural things to collect data, agih method and pairing method used to analyze this data. From the data analysis conducted, it was found that there were 152 directive speech acts, there were 5 types of directive speech acts namely invitation, command, prohibition, advice, advice. The results of the analysis in this article can provide further understanding of the role of directive speech acts in the context of video-based learning and material development by paying attention to directive speech acts.